Nicotine vaccines to treat tobacco dependence - Goniewicz, Maciej L. (Landes Bioscience, 2013)
Tobacco smoking is globally far more widespread than use of any other substance of abuse. Nicotine is an important tobacco constituent that is responsible for addictive properties of smoking. The currently available medications for the treatment of nicotine addiction have limited efficacy. A challenging novel therapeutic concept is vaccination against nicotine. An efficient vaccine would generate antibodies that sequester nicotine in the blood and prevent its access to the brain. The vaccine would have great potential for treating nicotine addiction and for relapse prevention. We reviewed the current status of vaccines against nicotine addiction that are undergoing clinical trials or are in preclinical development. We discuss problems associated with the development of nicotine vaccines, their efficacy in addiction treatment, challenges and ethical concerns. Existing evidence indicates that nicotine vaccination is well tolerated and capable of inducing an immune response but its effectiveness in increasing smoking abstinence has not been shown so far.